Security Issues and Weaknesses in Blockchain Cloud Infrastructure: A Review Article - Albaroodi, Hala A.; Anbar, Mohammed (Bright Publisher, 2025)
Cloud computing has become an essential technology due to its ability to provide scalable infrastructure and data services at a low cost and with minimal effort. It is widely adopted across various IT sectors and excels in providing flexible and scalable solutions for storage, computation, and networking. However, despite its widespread adoption, information security concerns remain a significant challenge, hampering its full potential. Issues such as data breaches, insufficient access controls, privacy risks, and vulnerability to external attacks persist, making security a critical obstacle for cloud computing’s growth. At the same time, blockchain technology has emerged as a promising solution for addressing these security challenges. Celebrated for ensuring data integrity, authenticity, and confidentiality, blockchain’s decentralized structure offers a potential safeguard against the risks cloud systems face. For instance, blockchain’s ability to maintain an immutable, tamper-proof ledger and decentralized control can mitigate unauthorised access risks, thereby enhancing cloud environments' transparency and security. One of the blockchain’s core components is the consensus protocol, a method through which a network of nodes validates transactions without needing to trust any single entity. In the case of Bitcoin, users follow the Proof of Work algorithm, dedicating hardware and energy resources to solve cryptographic puzzles and verify transactions. This decentralized verification process addresses fraud concerns, but it also brings challenges such as high energy consumption and network centralization, particularly in regions with cheap electricity. These concerns have led to worries about collusion risks and policy changes affecting the stability of the network. Blockchain’s decentralized nature has sparked significant interest, especially in its potential to enhance cloud computing security. Its ability to provide tamper-proof transaction logs, eliminate single points of failure, and grant users more control over data aligns well with the security demands of cloud environments. However, blockchain itself faces challenges, including scalability issues and its association with black-market trading due to its open-access model. Despite these concerns, blockchain’s integration into cloud systems presents a unique opportunity for addressing key security obstacles, thereby offering more robust solutions for corporate and financial applications.